TINJAUAN KONSEP DAN IMPLEMENTASI SISTEM SILVIKULTUR TPTII - Benteng Haposan Sihombing (Universitas 17 Agustus 1945 Samarinda, 2015)
Management of the world's forests are generally adopted within the meaning of the forest preservation and conservation of forest sustainability of forest resources. Management of natural forests in Kalimantan also adopted the concept of forest sustainability principles in which this principle is applied at the time of the commencement of the exploitation of natural tropical forests around the 1960s by the Company holders of forest concessions (HPH) or license holder Timber Forest Product Utilization (IUPHHK).Indonesian Silviculture Selective Logging Systems (TPTI) is considered having good in concept but in implementation in the field still shows shortcomings. It is caused by the variability of the type, condition and potential of the forest so diverse that a generalized silvicultural system is not appropriate. Hence it is necessary efforts to further implement silvicultural systems TPTI that have been and are applied in the field and look for other forms of more appropriate and based on the perspective that the forest silviculture applied in the production of natural forest management more precise application.